2018
DOI: 10.21037/apc.2018.02.01
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic intervals and pancreatic ductal adenocarcinoma (PDAC) resectability: a single-center retrospective analysis

Abstract: Background Pancreatic ductal adenocarcinoma (PDAC) often presents with nonspecific symptoms and the workup is not standardized. To study the impact of delays in diagnosis and in the initiation of treatment, we investigated the relationship between length of diagnostic intervals and surgical resectability. Methods We performed a retrospective chart review of patients evaluated for PDAC at Johns Hopkins in 2014. Data were collected on the patient (date of first symptoms—first medical appointment), diagnostic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Previous studies have mainly focussed on diagnostic delay as a determinant for upfront surgery, not as an outcome measure of multicentre workup. For example, in a retrospective study in a pancreatic centre the relationship between the diagnostic interval and surgical resectability in PDAC patients was studied [20]. A median diagnostic interval of 22 days (8e46 days) was reported, which was comparable to the monocentre group of our study, i.e.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies have mainly focussed on diagnostic delay as a determinant for upfront surgery, not as an outcome measure of multicentre workup. For example, in a retrospective study in a pancreatic centre the relationship between the diagnostic interval and surgical resectability in PDAC patients was studied [20]. A median diagnostic interval of 22 days (8e46 days) was reported, which was comparable to the monocentre group of our study, i.e.…”
Section: Discussionsupporting
confidence: 77%
“…In our study, patients treated in the public setting were less likely to have a pathologically confirmed diagnosis of pancreatic cancer or to receive any kind of cancer-directed therapy, took longer to be diagnosed or to start treatment, and were diagnosed at more advanced disease stages. Even though the impact of diagnostic and treatment delays in the outcomes of pancreatic cancer patients is debatable 16 20 , the fact that less patients treated in the public setting had their disease diagnosed in the resectable scenario, that these patients were less likely to receive anti-cancer therapy, and that they had inferior survival on adjusted analyses suggest that diagnostic and treatment delays might be harmful.…”
Section: Discussionmentioning
confidence: 99%
“…At first impression, the data on the health care assess in this population seem adequate in light of the results of investigations conducted in developed countries. Such studies have reported lower rates of pathological confirmation of cancer, ranging from 53 to 91% 21 , and median times from referral to treatment start of at least 30 days 16 , 18 . Also, in developed countries there is evidence that as few as one third of patients with pancreatic cancer are submitted to anti-cancer therapy 22 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…For a cohort of 116 patients with PDAC, Deshwar et al reported a median diagnostic time (time from first medical visit to diagnosis) of 22 days, and individuals with longer diagnostic times were significantly less likely to be suitable candidates for resection. 26 Meanwhile, delays in tissue biopsy are included among the list of negative effects by which the COVID-19 pandemic has impacted clinical care for patients with PDAC. 27 While WGS possesses the breadth to cover nearly all detectable mutations in a sample, ctDNA panels are subdivided into two main categories based on how their more limited catalog of ascertainable mutations are chosen.…”
Section: Challenges Faced By Molecular-targeted Clinical Trials In Pdacmentioning
confidence: 99%